AN OVERVIEW OF THE DEVELOPMENTS OF HALAL CERTIFICATION LAWS IN MALAYSIA, SINGAPORE, BRUNEI AND INDONESIA - Asa, Rokshana Shirin (Jurnal Syariah, 2019)
Halal is not solely a religious issue; it has reached the domain of halal trade and become a global halal trademark for quality affirmation. Today, halal has become a noteworthy issue in trading and trade related matters. Many countries consider halal as a new trademark for marketing. Halal labeling serves as a medium for strengthening the belief of Muslim consumers. It is a symbol of guaranteeing the purity of manufacturing the products. This promising large halal market has created an intensified attention around the world. Muslim and non-Muslim countries are developing their own halal matters, halal certification process, laws and regulations in order to compete for the global halal market. Countries with minority Muslim populations such as Singapore, the U.S.A, Canada, Japan, Australia, New Zealand and South Africa have become important providers to the world’s halal trade. For that reason, this article discusses the international initiatives taken by some Muslim and non-Muslim countries like Malaysia, Singapore, Brunei and Indonesia for the development of halal certification vis-a-vis their legal systems. Hence, the purpose of this discussion is to propose for better ways of implementing the Malaysian halal certification laws.